2019
DOI: 10.12659/msm.916121
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Can be a “Double-Edged Sword” for Chronic Kidney Disease Patients

Abstract: Excessive drinking of alcohol is becoming a worldwide problem, and people have recognized that there exists a close relationship between chronic kidney disease (CKD) and alcohol consumption. However, there are many inconsistencies between experimental and clinical studies on alcohol consumption and kidney damage. The possible reason for this contradictory conclusion is the complex drinking pattern of humans and some bioactivators in wine. In addition, the design itself of the clinical studies can also produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 121 publications
(210 reference statements)
1
21
0
4
Order By: Relevance
“…This study also found a significant correlation between alcohol consumption and CKD. Excessive alcohol consumption generally leads to liver damage but few studies have also found that ethanol can cause kidney damage 10 . Along with an unhealthy diet and lifestyle, heavy alcohol consumption can greatly contribute to CKD.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found a significant correlation between alcohol consumption and CKD. Excessive alcohol consumption generally leads to liver damage but few studies have also found that ethanol can cause kidney damage 10 . Along with an unhealthy diet and lifestyle, heavy alcohol consumption can greatly contribute to CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol induces production of free radicals [36-40] and also decreases antioxidant capabilities of enzymes in the kidney [41-43]. In a recent comprehensive review on clinical studies looking at links between CKD and alcohol consumption, Fan et al (2019) concluded that light-to moderate drinking may not have adverse effects on patients with CKD [44]. While the DSM-5 definition of AUD does not quantify alcohol consumption [45], NIAAA defines moderate drinking as “up to 1 drink per day for women and up to 2 drinks per day for men” whereas “binge drinking and heavy alcohol use can increase an individual’s risk of alcohol use disorder” [46].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol is highly caloric and excessive alcohol consumption can precipitate obesity and lead to obesity-related complications, including hypertension. Although the evidence of direct nephrotoxicity is lacking, many mechanisms of kidney injury associated with alcohol consumption have been proposed, including oxidative stress and renal disease caused by other systemic conditions [20].…”
Section: Secondary Hypertensionmentioning
confidence: 99%